Coping With Water Shortage: An Update on the Role of K+, Cl-, and Water Membrane Transport Mechanisms on Drought Resistance - Nieves-Cordones, Manuel; García-Sánchez, Francisco; Pérez-Pérez, Juan G.; Colmenero-Flores, Jose M.; Rubio, Francisco; Rosales, Miguel A. (Frontiers in Plant Science, 2019)
Drought is now recognized as the abiotic stress that causes most problems in agriculture, mainly due to the strong water demand from intensive culture and the effects of climate change especially in arid/semi-arid areas. When plants suffer water deficit (WD), a plethora of negative physiological alterations such as cell turgor loss, reduction of CO2 net assimilation rate, oxidative stress damage, and nutritional imbalances, among others, can lead to a decrease in the yield production and loss of commercial quality. Nutritional imbalances in plants grown under drought stress occur by decreasing water uptake and leaf transpiration, combined by alteration of nutrient uptake and long-distance transport processes. Plants try to counteract these effects by activating drought acclimatization mechanisms. Correct accumulation of salts and water constitutes an important portion of these mechanisms, in particular of those related to the cell osmotic adjustment and function of stomata. In recent years, molecular insights into the regulation of K+, Cl- and water transport under drought have been gained. Therefore, this article brings an update on this topic. Moreover, agronomical practices that ameliorate drought symptoms of crops by improving nutrient homeostasis will also be presented.